Respuesta :

1rstar
[tex]f(x) = \: {x}^{2} - 5x - 6 \\ \\ f(x) = \: {x}^{2} - 6x + x - 6 \\ \\ f(x) = \: (x - 6)(x + 1) = \: 0 \\ \\ || \: x = \: 6 || \: \: \: \: or \: \: \: || x = - 1 || \: \: \: \: \: Ans.[/tex]

Hope it helps you :)

The zeros of the polynomial function f(x) are x = 6 and x = -1.

Factorization method

Let the function f(x) be

[tex]$f(x)=x^{2}-5 x-6$[/tex]

By using the factorization method, we get

[tex]$f(x)=x^{2}-6 x+x-6$[/tex]

Note that -6 +1 = 5 and [tex]- 6 * 1 = - 6[/tex]

So we find: [tex]$f(x)=x^{2}-5 x-6$[/tex]

f(x) = (x-6)(x+1) = 0

[tex]$\|x=6\|$[/tex] and [tex]$\quad\|x=-1\|$[/tex]

Hence the zeros of the polynomial function f(x) are x = 6 and x = -1.

Therefore, the correct answer is option C. x = -6 and x = 1.

To learn more about the factorization method

https://brainly.com/question/11434122

#SPJ2